Hubungan Antara Keaktifan Berorganisasi Terhadap Prestasi Akademik pada Mahasiswa Program Studi Pendidikan Dokter Universitas Nusa Cendana - Kote, Angel Eddelweist Yubertina Febrina Bida; Ratu, Kristian; Nurina, Rr. Listyawati; Folamauk, Conrad Liab Hendricson (Universitas Nusa Cendana, 2023)
Background: Academic achievement is the result of learning obtained by students. One of the factors that influence academic achievement is organizational activity. Medical students tend to have low organizational activity as a result of the educational curriculum which causes lecture and practicum schedules to be more hectic than students of other study programs. Aim: Proving whether there is a relationship between organizational activity and academic achievement in students of the Medical Study Program, Universitas Nusa Cendana. Method: Observational analytic study with a case control design, which was conducted on students of the Medical Students at Universitas Nusa Cendana. Data on activeness in organizations was obtained by filling out the organizational activity questionnaire, while semester grade-point average data were obtained through the academic section of the Faculty of Medicine and Veterinary Medicine on 80 samples that met the inclusion criteria. Sampling was done by Stratified Random Sampling technique. The results were analyzed univariate and bivariate using the Coefficient Contingency test. Results: Data analysis from 80 samples showed that 73.75% of the samples had low organizational activity. Meanwhile, as many as 50% students have a semester grade-point average that is in the high category. The bivariate analysis with the Coefficient Contingency test show results p = 0.43 (p <0.05) on the relationship between organizational activity and academic achievement. Conclusion: There is no significant relationship between organizational activity and academic achievement among students of the Medical Study Program, Universitas Nusa Cendana.